EXPLORING STUDENTS’ PER CEPTION OF USING STORYBIRD ON ENGLISH WRITING SKILL - May Azura, Anisa; Salmiah, Maryati; Hidayat, Vian (JURNAL KONFIKS, 2025)
This qualitative study explores students’ perceptions of using Storybird to develop English writing skills among 18 intermediate-level students at SMA Negeri Binjai over a 10-week implementation period. Employing a mixed-methods approach, data were collected through structured questionnaires based on the Technology Acceptance Model (TAM) and Self-Determination Theory (SDT), as well as semi-structured interviews. The findings reveal that students’ perceptions were predominantly positive, with 81.1% reporting favorable views of Storybird. Creativity stimulation (88.8%) and increased motivation (87.5%) emerged as the platform’s strongest attributes. Students appreciated the visual storytelling approach for generating ideas, organizing writings more effectively, and facilitating collaborative learning. Challenges identified included platform navigation and internet connectivity issues. The study confirms that Storybird effectively supports three basic psychological needs autonomy, competence, and relatedness—enhancing intrinsic motivation and self-efficacy in writing. These findings contribute to the literature on technology-enhanced language learning and provide empirical support for using digital storytelling platforms in teaching English as a foreign language (EFL).